Restoration on Mixed Deciduous Forest at Mae Thang Watershed Conservation and Development Study Unit, Phrae Province - สุขปรุง ฐิตารีย์; แม่ลิ่ม สมพร; ทีจันทึก สคาร (Thai Journal of Science and Technology, 2021)
This study aimed to investigate the plant communities structure and composition, tree species Importance Value Index (IVI) and biomass for three areas as Mixed deciduous forest, Forest restoration at 30 years and Forest restoration at 15 years. The sample plots size 20m × 50m were settled for 3 plots in each area, which the total of 9 plots. The results showed, the total of tree species in all areas were 58 species, which in 47 genera and 22 families. In each areas was founded the important tree species as follows: Mixed deciduous forest namely, Tectona grandis, Schleichera oleosa and Xylia xylocarpa, whilst the Forest restoration at 30 years were Pterocarpus macrocarpus, Millettia brandisiana and Tectona grandis and the Forest restoration 15 years were Pterocarpus macrocarpus, Millettia brandisiana and Tectona grandis. The highest tree density was founded in Forest restoration at 30 years at 1,123 trees/ha. However, the total basal area was highest in Mixed deciduous forest at 33.70 m2/ha and the distribution of Diameter at Breast Height (DBH) was showed as an L-shape. Tree species diversity in all plant communities were at the moderate level varying between 2.64–2.58. The most similarity of plant communities was founded in between Forest restoration 15 years and mixed deciduous forest which 60.71%. Moreover, the study showed that the Forest restoration at 30 years has the highest above-ground biomass at 150.39 tons/ha.